Factors Associated with Delay First Medical Contact to Device Time in Patient with Acute ST-Segment Elevation Myocardial Infarction at Emergency Department, Nopparat Rajathanee Hospital - Chairat , Chalermpon (Journal of The Department of Medical Services, 2021)
Background : Patients with acute ST-segment elevation myocardial infarction (STEMI) should properly treat as soon as possible to decrease mortality. In 2017 for non-percutaneous coronary intervention capable hospital, the American Heart Association recommends the first medical contact (FMC) to device time should not exceed 120 minutes to achieve a better survival. Objective : To determine the factors associated with delayed first medical contact to device time >120 minutes in STEMI patients at the emergency department, Nopparat Rajathanee Hospital. Methods : A cross-sectional study was conducted in patients who were diagnosed with acute STEMI at the emergency department from January 2014 to September 2017. The patients were divided into two groups, first medical contact to device time ≤120 minutes and >120 minutes. The collected data includes age, sex, underlying diseases, presenting symptoms, emergency severity index (ESI), and complications. The factors associated with delay first medical contact to device time were analyzed by univariate and multivariate logistic regression. Results : 217 patients were enrolled. Male 173 patients (79.72%), female 44 patients (20.28%). The median time of FMC to device time was 178 minutes. The factors associated with delayed first medical contact to device time were ESI level 3 (OR 95% CI = 24.99 (3.2-202), p-value 0.003), and ESI level 4 (OR 95% CI = 12.29 (1.44-104), p-value 0.021). Conclusion : A miss evaluation from chief complaint symptom to ESI triage level 3 and 4 associated with delayed first medical contact to device time more than 120 minutes. An effective triage system and the further capable of percutaneous coronary intervention in the Nopparat Rajathanee Hospital will decrease the first medical contact to device time.